Mesoscopic study of cylindrical phases of poly(styrene)-poly(isoprene) copolymer: Order–order phase transitions by temperature control - Rodríguez-Hidalgo, María-del-Rosario; Soto-Figueroa, César; Martínez-Magadán, José-Manuel; Luís-Vicente (Polymer (Guilford), 2009)
Phase transitions of cylindrical structures of poly(styrene)–poly(isoprene) copolymer (PS–PI) toward spherical and gyroid structures were explored using DPD simulations and a coarse-grained model. Cylindrical phases were first obtained within a composition interval (“predominance region”) 0.2<fPS<0.26 (volume fraction of poly(styrene)). The predominance region of cylindrical structures was then subject to thermal heating cycles. The thermodynamic instabilities of cylindrical microdomains induce anisotropic composition fluctuations and phase transitions. A transition from the cylindrical phase at low composition limit to a spherical arrangement was observed during the thermal heating process. The cylindrical phase at the intermediate and high composition limit within the predominance region exhibits a transition towards a gyroid arrangement. The phase transition control during thermal heating on the cylindrical phases was governed by small variations in composition. The results are consistent with experimental studies. [Display omitted]